In vitro immunomodulatory effects of thymol and cinnamaldehyde in a pig intestinal epithelial cell line (IPEC-J2) - C. Shen; L.G. Christensen; P.B. Rasmussen; K.M. Kragh (Journal of Applied Animal Nutrition)
Thymol and cinnamaldehyde are phytogenic feed additives developed to improve gut health and growth performance in poultry and swine. This study evaluated the in vitro immune modulating effects of thymol and cinnamaldehyde blend (TCB) in a porcine gut epithelial cell line (IPEC-J2), with or without cellular damage caused by challenge with lipopolysaccharides. Cytotoxicity, permeability, wound-healing and bacteria adhesion assays were recorded. The expression of cytokines, tight junctions and polymeric immunoglobulin receptor (pIgR) were measured by RT-PCR. The IPEC-J2 cells were cultured in the presence of TCB at concentrations ranging from 1 ng/ml to 1 μg/ml and displayed high viability (>90%). TCB increased barrier integrity (13.8% less in lipopolysaccharide challenge which induced gut epithelial leakage, P<0.05) and accelerated the initial speed of wound recovery (day 1, 26% wound recovery in TCB treated vs 7% in control, P<0.05; day 2, 54 vs 39%, P<0.001). The RT-PCR analysis of cell culture showed that TCB upregulated anti-inflammatory cytokine interleukin (IL)-10 (73.3%, P<0.05) in non-stimulated IPEC-J2 cells, while, when stimulated, pIgR (9.7%, P<0.05) and tight junctions claudin-4 (9.4%, P<0.05) were upregulated by TCB. Furthermore, TCB significantly increased Lactobacillus acidophilus adherence to gut epithelial cells (285.0%, P<0.05). Overall, the current in vitro study showed that TCB can induce various immune responses, which may explain its in vivo benefits as feed additive.